Real-Time Air Quality Operational Forecasting Systems in Spain: an Application of the MM5-CMAQ-EMIMO Modelling System - San José, R.; Pérez, J.L.; Morant, J.L.; González Barras, R.M. (Física de la Tierra, 2008)
In this contribution we show the description, implementation and operation of an Operational Air Quality Forecasting System for industrial plants, urban and regional areas. The system is called OPANA (OPerational Atmospheric Numerical model for urban and regional Areas) and is the evolution and result of more than 10 years of research on sophisticated state-of-the-art numerical air quality modelling systems and the implementation on state-of-the-art computer platforms. The system is in operation since 2005 although older versions started to operate at the end of the 90’s. The OPANA tool is operating on different industrial plants in the south of Madrid area and also over urban areas such as Madrid (Spain), Leicester City (U.K.), Las Palmas de Gran Canaria (Canary Islands, Spain). OPANA modelling tool is actually operating with MM5 mesoscale meteorological model (PSU/NCAR, US) and the CMAQ (Community Multiscale Air Quality Modelling System) model developed by EPA (US). Additionally, a complex emission model (EMIMO) developed by our group in UPM (Spain) in 2001 is also described and needed to provide accurate hourly and high spatial resolution (1 km) pollution emission data at global level. Results show that these tools can provide reliable and robust information to authorities and industrial managers to control – in forecasting mode – the air quality in the surrounding areas of the industrial plant or to forecast the air quality in the whole city or region.